Non-exclusionary input prices - Nadimi, Soheil R.; Weisman, Dennis L. (My University, 2014)
This paper models a vertically-integrated provider that is a monopoly supplier of an input that is essential for downstream production. An input price that is “too high” can lead to inefficient foreclosure and one that is “too low” creates incentives for non-price discrimination. The range of non-exclusionary input prices is circumscribed by the input prices generated on the basis of upper-bound and lower-bound displacement ratios. The admissible range of the ratio of downstream to upstream price-cost margins is increasing in the degree of product differentiation and reduces to a single ratio in the limit as the products become perfectly homogeneous.
Keywords: Input prices; Vertical integration; Foreclosure; Sabotage